Estimativas de (Co)Variâncias e Tendências Genéticas para Pesos em um Rebanho Canchim - Mello, Silvio de Paula [UNESP]; Alencar, Maurício Mello de; Silva, Luiz Otávio Campos da; Barbosa, Rogério Taveira; Barbosa, Pedro Franklin (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 2002)
The objectives of this study were to estimate variances and covariances and to evaluate the genetic trends for body weight at birth (BW), weaning (WW) and twelve months of age (YW) in a Canchim (5/8 Charolais + 3/8 Zebu) herd. Data on 6.517 animals, born from 1953 through 1996, were used to estimate breeding values by the derivative free restricted maximum likelihood method, using a model that included the fixed effects of contemporary group (year-season of birth-sex of calf) and the covariable age of cow at calving (linear and quadratic effects), and the random additive direct, additive maternal and permanent environmental effects. Genetic trends for direct. maternal and total Maternal effects were estimated by the weighed regression of the annual (generation) breeding value (direct, maternal and total maternal) means on year (generation) of birth of the animals. The direct heritability estimates were equal to 0.39, 0.48 and 0.63 for BW. WW and YW. respectively, while the maternal heritabilities were, in the same order, equal to 0.03, 0.04 and 0.05, respectively. The annual direct genetic trends were equal to 0.046, 1.336 and 1.619 kg for BW, WW and YW, respectively, corresponding to 0.13, 0.66 and 0.75% of the herd means. By generation, the genetic trends were, in the same order, 0.269, 7.715 and 9.599 kg, respectively. The maternal and total maternal genetic trends were linear and positive. The results showed that the selection criteria used resulted in genetic progress for BW, WW and YW; however, the progress obtained was much smaller than the possible one.
Estimativas de (co) variâncias e tendências genéticas para pesos em um rebanho Canchim
Estimates of variances and covariances and genetic trends for body weights in a Canchim herd
Keywords: beef cattle; body weights; genetic trend